The plant-beneficial fungus Trichoderma harzianum T22 modulates plant metabolism and negatively affects Nezara viridula - Sara Van Hee; Alejandro E. Segurado Luchsinger; Antonino Cusumano; Joleen Masschelein; Hans Jacquemyn; Bart Lievens (BMC Plant Biology)
Abstract Background Plant-beneficial fungi play an important role in enhancing plant health and resistance against biotic and abiotic stresses. Although extensive research has focused on their role in eliciting plant defences against pathogens, their contribution to induced resistance against herbivorous insects and the underlying mechanisms remain poorly understood. In this study, we used insect bioassays and untargeted metabolomics to investigate the impact of root inoculation of sweet pepper with the plant-beneficial fungus Trichoderma harzianum T22 on direct defence responses against the insect herbivore Nezara viridula. Results We observed reduced relative growth rate of N. viridula on leaves of fungus-inoculated plants, with no change in mortality. Untargeted metabolomic analyses revealed that inoculation with T. harzianum did not affect the leaf metabolome in the absence of herbivory five weeks after inoculation. However, compared to non-inoculated plants, inoculated plants exhibited significant metabolic alterations in herbivore-damaged leaves following N. viridula feeding, while changes in the metabolic profile of distant leaves were less pronounced. Notably, metabolites involved in the shikimate-phenylpropanoid pathway, known to be involved in plant defence responses, displayed higher accumulation in damaged leaves of inoculated plants compared to non-inoculated plants. Conclusion Our results indicate that root inoculation with T. harzianum T22 affects plant defences against N. viridula, leading to reduced insect performance. Metabolite-level effects were primarily observed in damaged leaves, suggesting that the priming effect mainly results in localized metabolite accumulation at the site of attack. Future research should focus on identifying the detected compounds and determining their role in impairing N. viridula performance.